The Beiderbecke affair. Vol. 2 [videorecording (DVD)] - Reynolds, David; Smith, Frank W.; Bolam, James, 1935-; Flynn, Barbara, 1948-; Blakely, Colin (Distributed by Acorn Media, 2009)
It never occurs to Trevor that dishy blondes don't usually sell jazz records door-to-door. He orders a set of Bix Beiderbecke LPs but receives the wrong items. While trying to locate the missing music, he and his girlfriend, Jill, stumble upon black market goods in a church basement, secret meetings in a parking lot. They find corruption at the highest levels. Helping them out are a couple of friends, an overzealous police officer, an elderly snoop, and a town planner with a drawer full of incriminating files.